Manganese-Rich Nickel-Manganese-Cobalt Oxides as Hybrid Supercapacitor Electrode Materials - Tshivhase, Funanani (University of the Witwatersrand, Johannesburg, 2023)
Fossil fuels used as the conventional energy source play a substantial negative role in climatic changes and global warming. Their reservoirs on earth keep getting constrained, thus limiting their reliability. These issues make renewable energy sources an excellent alternative due to their abundance, environmental safety, affordability, and renewability. However, renewable energy is subjected to geographic limitations, and some sources are intermittent, which can be solved by applying energy storage devices. Asymmetric hybrid supercapacitors are an excellent choice due to the safety of aqueous electrolytes, exploitation of abundant metals in the metal oxides used, improvement of power and energy density and simple assembly and application. In this work, manganese-rich nickel-manganese-cobalt (MR-NMC) was studied and applied in asymmetric hybrid supercapacitors as a cathode material, and reduced graphene oxide (rGO) was used as an anode. Synthesis was done using co-precipitation-(Conv), laminar Taylor vortex flow reactor-(Lam), and microwave irradiation-(MW) approaches. Physical characterization was performed using XRD and TEM. Electrochemical studies were done using CV, GCD and EIS. Three full cells/two electrode systems were assembled and studied. Those cells were rGO//Conv MR-NMC, rGO//Lam MR-NMC and rGO//MW MR-NMC. The data obtained from electrochemistry tests was used for the calculations of specific capacitance, energy and power densities. rGO//MW MR-NMC cell had the highest specific capacitance response compared to rGO//Conv MR-NMC and rGO//Lam MR-NMC over the entire current density range used, where at the current density of 0.2 A g-1, rGO//MW MR-NMC had 44.77 F g-1, followed by rGO//Lam MR-NMC with 15,89 F g-1, then rGO//Conv MR-NMC with 13.68 F g-1. There was no significant difference in the specific capacitance responses of rGO//Conv MR-NMC and rGO//Lam MR-NMC. rGO//MW MR-NMC also exhibited higher energy density for the entire range of power density over rGO//Conv MR-NMC and rGO//Lam MR NMC. At the power density of 678,08 W kg-1, rGO//MW MR NMC had a specific energy density of 65 Wh kg-1, followed by rGO//Lam MR NMC with 23.45 Wh kg-1, then rGO//Conv MR-NMC with 19.82 Wh kg-1. Overall, the electrochemistry and the calculated perimeters thereafter showed that microwave irradiation is a reliable approach that can be used in the preparation of metal oxides used in energy storage devices for the improvement of electrochemical performance, which potentially enables the commercialization of these systems and management of energy crisis in South Africa, Africa and the world as a whole, hence the rGO//MW MR-NMC material performed better than the other two.
A dissertation submitted in the fulfilment of the requirements for the degree of Master of Science, to the Faculty of Sciences, School of Chemistry, University of the Witwatersrand, Johannesburg, 2023.
Keywords: LMR-NMC; MR-NMC; rGO; Laminar flow; Microwave irradiation; Hybrid supercapacitor; UCTD; SDG-9: Industry, innovation and infrastructure